'Humanitarian intervention', a predictable narrative? A comparative analysis of media narratives from Serbia to Syria. (December 2016) - Vukasovich, Christian; Dejanovic-Vukasovich, Tamara
This article examines the narratives produced in Associated Press, The New York Times and The Times (of London) reports surrounding key events in Kosovo and Syria, leading to calls for North Atlantic Treaty Organization (NATO) intervention, and the construction of perceptions and cultural memories of the conflicts in which they are wielded. The article argues that the narrative themes emerging from this coverage produced uncritical calls for military intervention that are limited and ubiquitous, narrowly delineated the options for response and understanding, relied heavily on press briefings of those that advocate military intervention (ignoring alternative voices), failed to provide deep-level analysis of the conflicts, and remained constant across all three media outlets and across both the Račak and Ghouta events. The article then examines the implications, arguing that the coverage can be understood as the deployment of weaponized media on a battlefield of public opinion and wielded in a way necessitating Western military action.